The interleukin 23 receptor gene does not confer risk to systemic sclerosis and is not associated with systemic sclerosis disease phenotype. Issue 2 (19th August 2008) - Rueda, B; Broen, J; Torres, O; Simeon, C; Ortego-Centeno, N; Schrijvenaars, M M V A P; Vonk, M C; Fonollosa, V; van den Hoogen, F H J; Coenen, M J H; Sanchez-Román, J; Aguirre-Zamorano, M A; et al.
Abstract : Objectives: Multiple studies indicate the role of the interleukin (IL)-17/IL-23 axis in autoimmune diseases, including systemic sclerosis (SSc). The aim of the current study was to investigate the possible implication of the IL23R gene in SSc susceptibility and/or clinical phenotype. Methods: An initial case–control study in 143 Dutch patients with SSc and geographically matched healthy individuals (n = 246) was carried out and followed by a replication study in a cohort of 365 Spanish patients with SSc and 515 healthy individuals. Seven single nucleotide polymorphisms (SNPs) spanning the IL23R gene were selected and genotyped using a Taqman assay. Results: Using a Dutch cohort of patients with SSc and controls we observed an association between two (rs11209032, rs1495965) of the seven tested SNPs and disease susceptibility (allelic p values: p = 0.02 and p = 0.01 respectively). However, a replication study in an independent Spanish cohort did not confirm these findings and reveal no association of any of the IL23R -tested SNP with disease susceptibility or clinical phenotype. Similarly, a meta-analysis considering both populations did not reveal any significant association. In addition, no association was observed between IL23R genetic variants and SSc clinical phenotypes. Conclusions: Our results suggest that the IL23R gene is not associated with SSc susceptibility or clinical phenotype.